Thrombotic and bleeding complications after orthopedic surgery - Oberweis, Brandon S.; Nukala, Swetha; Rosenberg, Andrew; Guo, Yu; Stuchin, Steven; Radford, Martha J.; Berger, Jeffrey S. (The American heart journal, 2013)
Thrombotic and bleeding complications are major concerns during orthopedic surgery. Given the frequency of orthopedic surgical procedures and the limited data in the literature, we sought to investigate the incidence and risk factors for thrombotic (myocardial necrosis and infarction) and bleeding events in patients undergoing orthopedic surgery. We performed a retrospective cohort analysis of 3,082 consecutive subjects ≥21 years of age undergoing hip, knee, or spine surgery between November 1, 2008, and December 31, 2009. Patient characteristics were ascertained using International Classification of Diseases, Ninth Revision, diagnosis coding and retrospective review of medical records, and laboratory/blood bank databases. In-hospital outcomes included myocardial necrosis (elevated troponin), major bleeding, coded myocardial infarction, and coded hemorrhage as defined by International Classification of Diseases, Ninth Revision, coding. Of the 3,082 subjects, mean age was 60.8 ± 13.3 years, and 59% were female. Myocardial necrosis, coded myocardial infarction, major bleeding, and coded hemorrhage occurred in 179 (5.8%), 20 (0.7%), 165 (5.4%), and 26 (0.8%) subjects, respectively. Increasing age (P < .001), coronary artery disease (P < .001), cancer (P = .004), and chronic kidney disease (P = .01) were independent predictors of myocardial necrosis, whereas procedure type (P < .001), cancer (P < .001), female sex (P < .001), coronary artery disease (P < .001), and chronic obstructive pulmonary disease (P = .01) were independent predictors of major bleeding. There is a delicate balance between thrombotic and bleeding events in the perioperative period after orthopedic surgery. Perioperative risk of both thrombosis and bleeding deserves careful attention in preoperative evaluation, and future prospective studies aimed at attenuating this risk are warranted.